Tensile and flexural strengths of coconut spathe-fibre reinforced epoxy composites - Sapuan, S.M.; Zan, M.N.M.; Zainudin, E.S.; Arora, Prithvi Raj (Journal of Tropical Agriculture, 2006)
Tensile and flexural strengths of coconut spathe and spathe-fibre reinforced epoxy composites were evaluated to assess the possibility of using it as a new material in engineering applications. Samples were fabricated by the hand lay up process (30:70 fibre and matrix ratio by weight) and the properties evaluated using the INSTRON Material Test System. Tensile and flexural strengths for the coconut spathe-fibre-reinforced composite laminates ranged from 7.9 to 11.6 MPa and from 25.6 to 67.2 MPa respectively, implying that the tensile strength of coconut spathe-fibre is inferior to other natural fibres such as cotton, coconut coir and banana fibres. However, fibre treatment may improve the interfacial bonding between fibre and matrix leading to better mechanical properties of the spathe-fibre-reinforced composite laminates.